2019
DOI: 10.1111/hsc.12754
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic inequality in joint‐pain medication use among community‐dwelling older adults in Israel

Abstract: Joint pain is a common experience among adults aged 65 and over. Although pain management is multifaceted, medication is essential in it. The paper examines the use of medication among older adults with joint pain in Israel and asks whether socioeconomic factors are associated with this usage. The data, harvested, from the Survey of Health, Aging and Retirement in Europe (SHARE), include 1,294 randomly selected community‐dwelling individuals aged 65 and over in Israel. Bivariate analysis and logistic regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…The study employs a quantitative approach, using data from the second, fourth and fifth ‘waves’ of SHARE (Survey of Health, Ageing and Retirement in Europe), conducted between 2006 and 2013 among people aged 50+ in 13 European countries and in Israel. SHARE was established as a longitudinal study meant to shed light on the changing demographic, health and economic trends in Europe (Achdut et al, (2015); Katz et al, 2015; Tur‐Sinai & Litwin, 2015; Lowenstein et al, 2019; Tur‐Sinai et al, 2019b). Within this ambit, men and women aged 50+ as well as their spouses were interviewed (Axelrad & Tur‐Sinai, 2020; Shuldiner et al, 2020; Silverstein et al, 2020; Tur‐Sinai et al, 2019a; Tur‐Sinai & Lewin‐Epstein, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…The study employs a quantitative approach, using data from the second, fourth and fifth ‘waves’ of SHARE (Survey of Health, Ageing and Retirement in Europe), conducted between 2006 and 2013 among people aged 50+ in 13 European countries and in Israel. SHARE was established as a longitudinal study meant to shed light on the changing demographic, health and economic trends in Europe (Achdut et al, (2015); Katz et al, 2015; Tur‐Sinai & Litwin, 2015; Lowenstein et al, 2019; Tur‐Sinai et al, 2019b). Within this ambit, men and women aged 50+ as well as their spouses were interviewed (Axelrad & Tur‐Sinai, 2020; Shuldiner et al, 2020; Silverstein et al, 2020; Tur‐Sinai et al, 2019a; Tur‐Sinai & Lewin‐Epstein, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…This study draws on data collected by the Survey of Health, Aging and Retirement in Europe (SHARE), which seeks to better understand the dynamics of the growing population of persons aged 50+ and to provide a research infrastructure for public policymaking on behalf of the older-adult population [35]. The data collected in SHARE make it possible to compare the health, economic situation, and welfare of older adults in 29 European countries over time by providing a multidisciplinary cross-national bank of microdata on health, psychological, and economic variables [36][37][38].…”
Section: Data Source and Study Samplementioning
confidence: 99%
“…Israel is among the countries with lowest proportion of the aged population among developed countries; 11 percent of the population is aged sixty-five or older (Tur-Sinai et al, 2019) and life expectancy at birth is high, men ranking fourth worldwide and women ninth in 2015 (Dwolatzky et al, 2017). The Israeli population of 9.0 million people (CBS, 2019a) is comprised of diverse ethnic groups, each characterised by unique cultural and social patterns (Clarfield et al, 2017).…”
Section: The Israeli Contextmentioning
confidence: 99%
“…• The findings may motivate healthcare policy-makers to discuss perceptions of health with patients and be attentive to patients who judge their health to be or become poor. (Clarfield et al, 2017;Tur-Sinai, et al, 2019), inequalities by gender, population group, and socioeconomic status in morbidity and mortality persist, including inequalities in SRH (CBS, 2019b). However, it has been demonstrated that the association of lower socioeconomic status (Daoud et al, 2009;Soskolne & Manor, 2010) or Arab population group (Benyamini et al, 2014) with poorer SRH is reduced or eliminated when psychosocial (e.g., mastery, depressive mood, social capital) and health behaviours factors are accounted for.…”
Section: What This Paper Addsmentioning
confidence: 99%
See 1 more Smart Citation